A Comparison of Two-Dimensional and Three-Dimensional Techniques for Kinematic Analysis of the Sagittal Motion of Sheep Hindlimbs During Walking on a Treadmill - Diogo, Camila Cardoso; Camassa, José Arthur; Fonseca, Bárbara; Maltez da Costa, Luís; Pereira, José Eduardo; Filipe, Vítor; Couto, Pedro Alexandre; Raimondo, Stefania; Armada-da-Silva, Paulo A.; Maurício, Ana Colette; Varejão, Artur S. P. (Frontiers in Veterinary Science, 2021)
Compared to rodents, sheep offer several attractive features as an experimental model for testing different medical and surgical interventions related to pathological gait caused by neurological diseases and injuries. To use sheep for development of novel treatment strategies in the field of neuroscience, it is key to establish the relevant kinematic features of locomotion in this species. To use sheep for development of novel treatment strategies in the field of neuroscience, it is crucial to understand fundamental baseline characteristics of locomotion in this species. Despite their relevance for medical research, little is known about the locomotion in the ovine model, and next to nothing about the three-dimensional (3D) kinematics of the hindlimb. This study is the first to perform and compare two-dimensional (2D) and 3D hindlimb kinematics of the sagittal motion during treadmill walking in the ovine model. Our results show that the most significant differences took place throughout the swing phase of the gait cycle were for the distal joints, ankle and metatarsophalangeal joint, whereas the hip and knee joints were much less affected. The results provide evidence of the inadequacy of a 2D approach to the computation of joint kinematics in clinically normal sheep during treadmill walking. The findings from the present investigation are likely to be useful for an accurate, quantitative and objective assessment of functionally altered gait and its underlying neuronal mechanisms and biomechanical consequences.